Sclerosis and blisters: An uncommon association revealing a new case of bullous morphea - Soraya Aouali; Saida Sefraoui; Kaoutar Sof; Siham Dikhaye; Nada Zizi (Our Dermatology Online, 2021)
Bullous morphea is a rare variant of localized scleroderma (morphea) characterized by subepidermal bullae developed over sclerotic plaques. The pathogenesis of bullae formation has been the subject of several debates, which arrived at the conclusion of a multifactorial mechanism. We report the case of a 67-year-old patient with bullous morphea of the trunk and thighs, who showed a good response to PUVA therapy combined with topical steroids. Our case report supports the efficiency of PUVA therapy associated with topical steroids as a safe regimen compared to other therapeutic approaches.